Zero‐pseudorandom noise training OFDM. Issue 9 (1st April 2014) - Esmaiel, H.; Jiang, D.
Abstract : A novel transmission scheme called zero‐pseudorandom noise training sequence orthogonal frequency division multiplexing (ZPN‐OFDM) is proposed, where the frame structure of dual‐pseudorandom noise (PN) padding time domain synchronous OFDM is modified by replacing the first PN sequence by a zero sequence. The new ZPN‐OFDM system offers better energy efficiency than previous OFDM systems. The ZPN‐OFDM system is tested for significant tap delay multipath channels. Simulation results show that ZPN‐OFDM can provide significant bit error rate improvement as well as energy efficiency improvement.